Photo of an architectural rendering of the Mines Building, Alaska Yukon Pacific Exposition, Seattle, 1908. - Nowell, Frank H., 1864-1950 (1908)
Caption on image: [illeg.] and Huntington, Architects. Mines Building, Alaska-Yukon Pacific Exposition, Seattle, Wash. PH Coll 727.477 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number